The impact of financing contracts on the profitability of Islamic banks - Maisyarah Stapah @ Salleh,; Bayu Taufiq Possumah,; Nizam Ahmat, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper investigates the impact of financing contracts on Net Profit Margin (NPM) of the Islamic banks. Focussing on two financing contracts of Bai’ Bithaman Ajil (BBA) and Al-Ijarah Thumma Al-Bai’ (AITAB), the paper employs static panel data of Malaysian banks over 2008 to 2018. Controlling for bank and market-specific factors, the results indicated that AITAB exerted significant impact on the NPM. The paper further found that risk aversion, operating cost, liquidity and asset quality improves the NPM. In addition, the results show that the market structure influence the level of NPM. The Islamic banks may control these variables in setting for their preferred NPM level. Finally, the banks may need to carefully examine the types of financing contracts offered as they have different characteristics and may affect NPM.